Outsiders within : writing on transracial adoption - Trenka, Jane Jeong, 1972-; Oparah, Julia Chinyere; Shin, Sun Yung (University of Minnesota Press, 2021)
"Confronting trauma behind the transnational adoption system-now back in print. Many adoptees are required to become people that they were never meant to be. While transracial adoption tends to be considered benevolent, it often exacts a heavy emotional, cultural, and economic toll on those who directly experience it. Outsiders Within is a landmark publication that carefully explores this most intimate aspect of globalization through essays, fiction, poetry, and art. Moving beyond personal narrative, transracially adopted writers from around the world tackle difficult questions about how to survive the racist and ethnocentric worlds they inhabit, what connects the countries relinquishing their children to the countries importing them, why poor families of color have their children removed rather than supported-about who, ultimately, they are. In their inquiry, the contributors unseat conventional understandings of adoption politics, reframing the controversy as a debate that encompasses human rights, peace, and reproductive justice."-- Provided by publisher.
"With a new preface"--Cover
Keywords: Interracial adoption.; Adoption interraciale.; Essays.; SOCIAL SCIENCE.; BIOGRAPHY & AUTOBIOGRAPHY.; Interracial adoption